Imposter Syndrome and Adoption Readiness for Network Pharmacology: The Mediating Role of Training and Moderating Role of Peer Support - Kumari, Tiyagura Nagaraja; Babu, Bachunaga Kishore; Pilli, Daniel; Giddaiah, Repalle; Sowjanya, K. (International Journal of Pharmaceutical Investigation, 2026)
Background Network pharmacology provides a comprehensive systems-level framework for the domains of drug discovery, precision medicine, and the repurposing of therapeutics. Despite the rapid advancement of technology, the psychological readiness of healthcare professionals has gotten less attention. Imposter Syndrome (IS), a condition marked by persistent self-doubt inspite of demonstrated competence, may hinder the incorporation of such cutting-edge instruments. Aim The objective of this study was to investigate the influence of IS on the readiness to adopt network pharmacology tools, while also assessing the mediating role of training adequacy and the moderating influence of peer support. Materials and Methods validated tools used to assess IS, adoption readiness, training adequacy, and peer support, 450 doctors, pharmacists, and researchers from Andhra Pradesh participated in a survey. We used regression, mediation, and moderation models to analyse the data. Results The findings showed a negative correlation between IS and adoption readiness. (β=-0.39, R²=0.17, p<0.001). Training adequacy (β=-0.12, p<0.001) and institutional culture (β=-0.09, p<0.01) were found to partially mediate this relationship, whereas peer support acted as a moderator (interaction β =0.16, p=0.001). Conclusion Social and psychological support networks are just as important to the effective implementation of network pharmacology as technical training. In order to lessen the negative effects of IS and increase healthcare professionals' confidence and readiness to use cutting-edge pharmaceutical tools, comprehensive training programs and strong peer networks are crucial.
Keywords: Adequate Training; Imposter Syndrome; Network Pharmacology; Technology Adoption